The global, regional, and national burden of cirrhosis by cause in 195 countries and territories, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017. (March 2020) - ; Sepanlou, Sadaf G; Safiri, Saeid; Bisignano, Catherine; Ikuta, Kevin S; Merat, Shahin; Saberifiroozi, Mehdi; Poustchi, Hossein; Tsoi, Derrick; Colombara, Danny V; Abdoli, Amir; Adedoyin, Rufus Adesoji; et al.
Summary: Background: Cirrhosis and other chronic liver diseases (collectively referred to as cirrhosis in this paper) are a major cause of morbidity and mortality globally, although the burden and underlying causes differ across locations and demographic groups. We report on results from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 on the burden of cirrhosis and its trends since 1990, by cause, sex, and age, for 195 countries and territories. Methods: We used data from vital registrations, vital registration samples, and verbal autopsies to estimate mortality. We modelled prevalence of total, compensated, and decompensated cirrhosis on the basis of hospital and claims data. Disability-adjusted life-years (DALYs) were calculated as the sum of years of life lost due to premature death and years lived with disability. Estimates are presented as numbers and age-standardised or age-specific rates per 100 000 population, with 95% uncertainty intervals (UIs). All estimates are presented for five causes of cirrhosis: hepatitis B, hepatitis C, alcohol-related liver disease, non-alcoholic steatohepatitis (NASH), and other causes. We compared mortality, prevalence, and DALY estimates with those expected according to the Socio-demographic Index (SDI) as a proxy for the development status of regions and countries. Findings: In 2017, cirrhosis caused more than 1·32 million (95% UI 1·27–1·45) deaths (440 000 [416 000–518 000; 33·3%] in females and 883 000 [838 000–967 000; 66·7%] in males) globally, compared with less than 899 000 (829 000–948 000) deaths in 1990. Deaths due to cirrhosis constituted 2·4% (2·3–2·6) of total deaths globally in 2017 compared with 1·9% (1·8–2·0) in 1990. Despite an increase in the number of deaths, the age-standardised death rate decreased from 21·0 (19·2–22·3) per 100 000 population in 1990 to 16·5 (15·8–18·1) per 100 000 population in 2017. Sub-Saharan Africa had the highest age-standardised death rate among GBD super-regions for all years of the study period (32·2 [25·8–38·6] deaths per 100 000 population in 2017), and the high-income super-region had the lowest (10·1 [9·8–10·5] deaths per 100 000 population in 2017). The age-standardised death rate decreased or remained constant from 1990 to 2017 in all GBD regions except eastern Europe and central Asia, where the age-standardised death rate increased, primarily due to increases in alcohol-related liver disease prevalence. At the national level, the age-standardised death rate of cirrhosis was lowest in Singapore in 2017 (3·7 [3·3–4·0] per 100 000 in 2017) and highest in Egypt in all years since 1990 (103·3 [64·4–133·4] per 100 000 in 2017). There were 10·6 million (10·3–10·9) prevalent cases of decompensated cirrhosis and 112 million (107–119) prevalent cases of compensated cirrhosis globally in 2017. There was a significant increase in age-standardised prevalence rate of decompensated cirrhosis between 1990 and 2017. Cirrhosis caused by NASH had a steady age-standardised death rate throughout the study period, whereas the other four causes showed declines in age-standardised death rate. The age-standardised prevalence of compensated and decompensated cirrhosis due to NASH increased more than for any other cause of cirrhosis (by 33·2% for compensated cirrhosis and 54·8% for decompensated cirrhosis) over the study period. From 1990 to 2017, the number of prevalent cases more than doubled for compensated cirrhosis due to NASH and more than tripled for decompensated cirrhosis due to NASH. In 2017, age-standardised death and DALY rates were lower among countries and territories with higher SDI. Interpretation: Cirrhosis imposes a substantial health burden on many countries and this burden has increased at the global level since 1990, partly due to population growth and ageing. Although the age-standardised death and DALY rates of cirrhosis decreased from 1990 to 2017, numbers of deaths and DALYs and the proportion of all global deaths due to cirrhosis increased. Despite the availability of effective interventions for the prevention and treatment of hepatitis B and C, they were still the main causes of cirrhosis burden worldwide, particularly in low-income countries. The impact of hepatitis B and C is expected to be attenuated and overtaken by that of NASH in the near future. Cost-effective interventions are required to continue the prevention and treatment of viral hepatitis, and to achieve early diagnosis and prevention of cirrhosis due to alcohol-related liver disease and NASH. Funding: Bill & Melinda Gates Foundation.